Spatial Resilience and Institutional Adaptation: Assessing the Role of Local Inter-Faith Forums in Regional Social Stability - Sri Haryaningsih; Farah Devi Andriani; Parlindungan Parlindungan; Dita Purnama (Sean Institute, 2026)
Urban and regional planning literature increasingly recognizes that territorial resilience relies not only on physical infrastructure but also on the adaptive capacity of local social institutions. In multi-faith, rapidly urbanizing regions, social friction often exhibits distinct geographical patterns, making institutional spatial awareness critical for maintaining peace. This study evaluates how local inter-faith forums adapt institutionally and spatially to safeguard regional social stability. Utilizing a qualitative research design rooted in Interpretative Phenomenological Analysis (IPA), data were gathered through semi-structured interviews (n=24) and three Focus Group Discussions with community leaders, regional administrators, and peace advocates. Analyzed via NVivo, the findings reveal that successful conflict mitigation depends on